MENINGKATKAN HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MELALUI METODE TEACHING GAMES FORUNDERSTANDING ( TGFU ) PADA SISWA KELASVII.7 SEKOLAH MENENGAH PERTAMA NEGERI 14 PADANG - Putri Lolita Yanavia; Khairuddin; Sri Gusti Handayani; Yuni Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of Grade VII.7 students in Physical Education, Sports, and Health (PJOK) at SMP Negeri 14 Padang. The issues stemmed from a lack of variety in teaching methods, low student engagement, and limited facilities and infrastructure. The study aimed to improve PJOK learning outcomes through the implementation of the Teaching Games for Understanding (TGfU) model. A Classroom Action Research (CAR) design was employed, utilizing the Kemmis and McTaggart model, which comprises the stages of planning, implementation, observation, and reflection. The research was conducted over two cycles—each consisting of two meetings—involving 32 students. Data collection involved observation, learning outcome tests, and documentation, while data analysis utilized quantitative descriptive methods. The results indicated an improvement in student learning outcomes across both cycles. In Cycle I, the average score rose from 70 to 75.63 (a 5.6% increase). In Cycle II, the average score rose from 80 to 88.1 (an 8.1% increase). Furthermore, the percentage of students achieving mastery learning also showed a significant increase. Thus, it can be concluded that implementing the Teaching Games for Understanding (TGfU) model is effective in enhancing PJOK learning outcomes and fostering an active, enjoyable, and meaningful learning experience for students.